2020
DOI: 10.1364/josaa.382228
|View full text |Cite
|
Sign up to set email alerts
|

Observer metamerism in commercial displays

Abstract: Two uniform patches presented on two displays under identical viewing conditions can appear as the same color to one observer but as mismatched colors to another observer. This phenomenon, called observer metamerism (OM), occurs due to individual differences in color matching functions. To avoid its potentially adverse impacts in display calibration and characterization, it is desirable to have a predictive model of OM. In this work, we report the computational results of how to use existing metrics to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Moreover, changing the primary set was also found to cause observer metamerism, a phenomenon that the color appearance of a pair of color stimuli composed of two primary sets appear to match to one observer, but mismatch to other observers. It was found that the degrees of observer metamerism (i.e., the variations of color differences perceived by different observers) varied with the primary sets [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, changing the primary set was also found to cause observer metamerism, a phenomenon that the color appearance of a pair of color stimuli composed of two primary sets appear to match to one observer, but mismatch to other observers. It was found that the degrees of observer metamerism (i.e., the variations of color differences perceived by different observers) varied with the primary sets [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several possible metrics, which have been examined in previous works 13,33 as a metamerism index or metric, were considered: goodness‐of‐fit coefficient (GFC), 34 spectral correlation angle (SCA), and spectral angle mapper (SAM) 35 . These metrics are commonly based on comparing spectral similarity between spectral curves.…”
Section: Resultsmentioning
confidence: 99%
“…In order to verify the performance of the four metrics (SAM, SCA, GFC, and OMM N ), the OMM indices of the 28 example display pairs with a peak luminance of 1000 cd/m 2 and outputs of the metrics were compared. Additionally, the SPDs of seven commercial displays from Xie's work 13 were included to use for evaluation in the same manner. It should be noted that the seven commercial displays resulted in 21 display pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of modern color science and technology, there are more techniques and methods to reproduce colors, such as light-emitting diodes (LEDs) and lasers that are spectrally narrow band, magnifying the individual differences in color-matching functions (CMFs). In that case, the observers with normal color vision will have different color perceptions (named color inconstancy) [1] and different color differences (named observer metamerism) [2], [3] under the same viewing conditions.…”
Section: Introductionmentioning
confidence: 99%